Cattle-derived knob paratopes grafted onto peripheral loops of the IgG1 Fc region enable the generation of a novel symmetric bispecific antibody format - Yanakieva, Desislava; Vollmer, Lena; Evers, Andreas; Siegmund, Vanessa; Arras, Paul; Pekar, Lukas; Doerner, Achim; Valldorf, Bernhard; Kolmar, Harald; Zielonka, Stefan; Krah, Simon (Frontiers in Immunology, 2023)
In this work we present a novel symmetric bispecific antibody format based on engraftments of cattle-derived knob paratopes onto peripheral loops of the IgG1 Fc region. For this, knob architectures obtained from bovine ultralong CDR-H3 antibodies were inserted into the AB loop or EF loop of the CH3 domain, enabling the introduction of an artificial binding specificity into an IgG molecule. We demonstrate that inserted knob domains largely retain their binding affinities, resulting into bispecific antibody derivatives versatile for effector cell redirection. Essentially, generated bispecifics demonstrated adequate biophysical properties and were not compromised in their Fc mediated functionalities such as FcRn or FcγRIIIa binding.